2023
DOI: 10.3390/ijerph20043513
|View full text |Cite
|
Sign up to set email alerts
|

Association between Polymorphisms of Hemochromatosis (HFE), Blood Lead (Pb) Levels, and DNA Oxidative Damage in Battery Workers

Abstract: Occupational exposure to lead (Pb) continues to be a serious public health concern and may pose an elevated risk of genetic oxidative damage. In Brazil, car battery manufacturing and recycling factories represent a great source of Pb contamination, and there are no guidelines on how to properly protect workers from exposure or to dispose the process wastes. Previous studies have shown that Pb body burden is associated with genetic polymorphisms, which consequently may influence the toxicity of the metal. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…However, a study accomplished on 36 Spanish patients C282Y and H63D mutations showed no differences between patients healthy people [33]. Another study mentioned to the relation between HFE polymorphisms and DNA damage by oxidative agents [34]. Further, a study found that C282Y mutation causes overload of serum ferritin level at 482 μg/L in female [35].…”
Section: Resultsmentioning
confidence: 99%
“…However, a study accomplished on 36 Spanish patients C282Y and H63D mutations showed no differences between patients healthy people [33]. Another study mentioned to the relation between HFE polymorphisms and DNA damage by oxidative agents [34]. Further, a study found that C282Y mutation causes overload of serum ferritin level at 482 μg/L in female [35].…”
Section: Resultsmentioning
confidence: 99%